UCP3 gene polymorphism and insulin resistance in obese female adolescents - Dian Eurike; Harry Freitag Luglio Muhammad; Rina Susilowati; Madarina Julia (Paediatrica Indonesiana, 2012)
Background A previous study on obese female adolescents inYogyakarta done in the year 2007 suggests that genetic factorsmight influence insulin resistance. One genetic factor that hasbeen associated \\lith insulin resistance in other populations isthe ô€55C;T polymorphism in the uncoupling protein 3 (UCP3)gene.Objective To investigate an association between the ô€55C;Tpolymorphism in the UCP3 gene and insulin resistance in obesefemale adolescents in Yogyakarta.Methods A total of79 obese female adolescents were enrolled inthis crossô€sectional study. Genotyping of the ô€ 5 SC/T polymorphismin the UCP3 gene was performed by polymerase chain reactionô€restriction fragment length polymorphism (PCRô€RFLP).Results The TiT homozygous individuals had a higher risk ofinsulin resistance (OR 2.3; 95% CI 0.4 to 14.1), as well as higherfasting insulin concentration and homeostatic model assessmentfor insulin resistance (HOMAô€IR) compared to individuals v.ithother genotypes. The T allele carriers also had a higher risk ofinsulin resistance (OR 1.3; 95% CI 0.7 to 2.5), as well as higherfasting insulin concentration and HOMAô€ IR compared to Callele carriers. However, none of these results were statisticallysignificant (P > 0.05).Conclusion The TiT genotype and T allele of the UCP3 geneô€55CiT polymorphism was not significantly associated increasedrisk of insulin resistance in obese female adolescents in Yogyakarta.[Paediatr lndanes. 2012;52:152-6].